Developing A Digital Learning Game as a Medium for Cultural Enrichment on Descriptive Text - Crisdiana, Reny (Soegijapranata Catholic University, 2019)
This study is aimed to develop a digital learning game as a medium to enrich students’ insight about their local culture embedded in descriptive text material. Adapting “system approach” model designed by Dick and Carey, this study employed need analysis, material development and formative evaluation as steps to develop the product. The need analysis was conducted by analyzing the documents, administering questionnaires to the students and interviewing the teachers. The material development was done by designing blueprint of the product’s content, pictures and sound in the computer applications. The formative evaluation consisted of the theoretical validation and empirical validation. The result of the theoretical validation was classified into four categorizes involving multimedia, language content, cultural and pedagogical aspect. The multimedia validator graded the most criteria of the game’s design and layout in a very good scale. The language content validator graded the most criteria of the learning game’s content in balance between “very good” and “good” scale. The cultural aspect had been validated by the natives of mentioned places, consisting of a native of Java, Bali and Flores. Lastly, the pedagogical aspect was validated by two teachers who taught seventh grade and eighth grade at SMPN 26 Surabaya. Both teachers graded the digital learning game in a “very good” scale. Those final scales obtained after some revisions from validators had been finished. The result of empirical validation was obtained from the tryout of the product to fifteen students of SMPN 26 Surabaya. The result of the empirical validation showed that the students have positive responds to the developed learning game. It was concluded from the most scales given by the students including “very good” and “good” scale for the mentioned criteria. In conclusion, the digital learning game has met its final product to be used by the students to learn culture for descriptive text material.